Comparison of 25-hydroxyvitamin D levels in exclusively and non-exclusively breastfed infants - Analysa Margaretha Bogar; Helena Anneke Tangkilisan; Hesti Lestari (Paediatrica Indonesiana, 2012)
Background Vitamin D is an essential nutrient for theprevention of rickets. Human milk typically contains a vitaminD concentration of 25 lUlL or less. Breastfed infants are at riskof vitamin D deficiency. Previous studies conducted in countrieswith four seasons have reported that risk factors associated withvitamin D deficiency influence the vitamin D status in exclusivelybreastfed infants.Objective To compare the levels of 25-hydroxyvitamin D(25 (OH)D) in exclusively and non-exclusively breastfed in-fants.Methods This cross-sectional study was conducted in SingkilDistrict, Manado from February to May 2011. Of 48 Posyandu(Integrated Health Center), 4 were chosen to be the sourcesof subjects for this study. Subjects were collected consecutivelyamong infants aged 6-7 months. The resulting exclusively andnon-exclusively breastfed groups had 36 infants each.Results The mean 25 (OH)D level in the exclusively breastfedgroup was 61.75 nmoliL (95% CI 58.02 to 65.48) and in the nonexclusivelybreastfed group was 85.09 nmollL (95% CI 79.49 to90.68). The difference in 25 (OH)D levels in the two groups wasstatistically significant. However, 25 (OH)D levels of both groupswere Mthin the normal range.Conclusion The 25 (OH)D level was significantly lower in ex-clusively breastfed infants compared to that in non-exclusivelybreastfed infants, but both levels were still in the normal range.[Paediatr rndones. 2012;52:157-60].